2013
DOI: 10.2169/internalmedicine.52.9366
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Class IV+V Lupus Nephritis with Combination Therapy of High-dose Corticosteroids, Tacrolimus and Intravenous Cyclophosphamide

Abstract: A substantial number of patients with lupus nephritis (LN) are refractory to conventional glucocorticoid (GC) treatment. Although many of these patients respond to immunosuppressive drugs such as intravenous cyclophosphamide (IVCY), azathioprine (AZA), mizoribine, tacrolimus, cyclosporine A (CSA) and mycofenolate mofetil (MMF), some remain refractory to such therapies. Recent studies of multi-target therapies have reported effective outcomes for immunosuppression following renal transplantation and refractory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Bao et al [19] first reported in 2008 that tacrolimus plus MMF could achieve a higher complete remission rate within 24 weeks than CYC (50% vs. 5%, p < .05) [19] in the treatment of mixed diffuse proliferative and membranous LN (class III or IV þ V). Recently, we reported a prospective, open-label, single-center, pilot study of a multi-target therapy comprising CYC and tacrolimus [20]. In this study prednisolone (PSL) was started at a dose of 0.6-1.0 mg/kg/ day for 2 weeks and 500 mg of intravenous CYC was administered biweekly for 3 months (six times) with 3 mg/day of tacrolimus daily.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Bao et al [19] first reported in 2008 that tacrolimus plus MMF could achieve a higher complete remission rate within 24 weeks than CYC (50% vs. 5%, p < .05) [19] in the treatment of mixed diffuse proliferative and membranous LN (class III or IV þ V). Recently, we reported a prospective, open-label, single-center, pilot study of a multi-target therapy comprising CYC and tacrolimus [20]. In this study prednisolone (PSL) was started at a dose of 0.6-1.0 mg/kg/ day for 2 weeks and 500 mg of intravenous CYC was administered biweekly for 3 months (six times) with 3 mg/day of tacrolimus daily.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Frequently relapsing nephrotic syndrome refers to at least two relapses during treatment within six months or more than three relapses within 12 months of the initial presentation. 1,2 It is a common nephropathic disease. It has different pathological types.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported successful treatment of LN patients who did not respond to IV-CYC by adding TAC. 32 Sakai's study showed that the combination of TAC (3.0 mg/day) and CYC resulted in a signi cantly higher CR rate after 6 months compared to CYC alone. 33 Our study provides a clearer separation of TAC doses compared with previous studies and con rms the multiplicative interaction between different doses of TAC and CYC.…”
Section: Discussionmentioning
confidence: 99%